Efektivitas Terapi Storytelling terhadap Penurunan Kecemasan Anak Prasekolah Selama Hospitalisasi di Rumah Sakit Sumber Hidup Ambon - Vernando Yanry Lameky; Nenny Parinussa (Direktorat Politeknik Kesehatan Makassar, 2025)
Background: Hospitalization can trigger significant anxiety in preschool children due to their cognitive and emotional limitations in understanding medical procedures. Storytelling therapy is a potential non-pharmacological approach to alleviating anxiety, especially in regions such as Maluku, which have limited resources and a unique cultural context. Method: This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 38 children aged 3–5 years hospitalized at Sumber Hidup Hospital in Ambon were selected through total sampling. The intervention, which involved storytelling therapy, was conducted over five consecutive days within two weeks, with each session lasting approximately 30 minutes, resulting in a total intervention duration of around 2.5 hours per child. The instrument used was the Spence Children’s Anxiety Scale (SCAS) preschool version. Data analysis was performed using a paired t-test. Results: The average anxiety score decreased from 3.08 to 2.37 (∆ = 0.71), with statistical test results showing a p-value of 0.001 and a 95% confidence interval of 0.525–0.896, indicating a statistically significant decrease. Most children moved from the moderate/severe anxiety category to the mild category after the intervention. Conclusion: Storytelling therapy was proven effective in reducing anxiety in preschool children during hospitalization and is worthy of integration into pediatric nursing practice in island regions such as Maluku. However, the limitation of the design without a control group should be noted in interpreting the results. These findings have practical implications that culturally-based narrative interventions can serve as a simple, cost-effective, and contextually appropriate strategy in pediatric nursing care. Keywords: Play Therapy; Storytelling; Child Anxiety; Hospitalization; Maluku